Aerodynamics of ski jumping - Virmavirta, M. (The engineering approach to winter sports, 2016)
Ski jumping is an exciting and primarily competitive sport involving both ballistic and aerodynamic factors. The ballistic factors are release velocity and release position of a ski jumper from the take-off table, whereas aerodynamic factors include the gliding properties of the jumper/ski system (velocity, suit design, surface area, posture of the jumper/ski system, resisting and lifting forces). Both ballistic and aerodynamic factors place special demands on the jumper so that he/she can, for example, optimally maximize the vertical lift and minimize the drag forces. Ski jumping has attracted spectators 200 years and it has undergone several notable steps in the development of performance technique and equipment. This text does not try to provide any complete examination of prior work in this area, but some well-known studies and surveys/reviews will be given.